EFEKTIVITAS KURIKULUM BERBASIS TEKNOLOGI TERHADAP MOTIVASI DAN PRESTASI BELAJAR SISWA SEKOLAH DASAR - Nina Mekalungi; Fitri Puji Rahmawati; Anik Ghufron (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to examine the effectiveness of technology-based curriculum on elementary school students' motivation and academic achievement. The method used in this study is literature review. The research procedure was conducted by gathering scientific articles from various sources, such as academic journals, books, and other relevant scholarly publications on the research topic. Data collection was systematically conducted using search engines such as Google Scholar and other research databases. The results of the study indicate that the integration of technology into elementary education curriculum has a significant positive impact on students' interest, motivation, and academic achievement.